TRANSFORMASI SUPERVISI MANAJERIAL UNTUK MENINGKATKAN MUTU PENGELOLAAN DI SD NEGERI 3 BANDA ACEH - Musriadi; Syarfuni; Akmaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the implementation of managerial supervision in improving the quality of management in SD Negeri 3 Banda Aceh. The research method used is descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentary studies. The research respondents are the school principal, teachers, and school staff involved in the managerial supervision process. Data analysis technique uses the interactive model by Miles and Huberman. The research findings indicate that the implementation of managerial supervision in SD Negeri 3 Banda Aceh still faces several challenges, including a lack of deep understanding of managerial supervision concepts, resource constraints, and a lack of training for supervisors. However, efforts have been made to improve the quality of school management through managerial supervision activities, such as teacher mentoring, curriculum development, and school resource management. The implications of this research are the need to improve the understanding and managerial skills of school supervisors, as well as the expansion of resources and support for effective implementation of managerial supervision to improve the quality of management in SD Negeri 3 Banda Aceh.